ANALISIS EKUITAS MEREK DARI KATEGORI PRODUK MINYAK GORENG BIMOLI PADA KELOMPOK USAHA INDOFOOD - Bambang Hadi Santoso (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2005)
The Indofood Group and even all companies at the present time are facing tight competition. As a consequence of this condition, they must have abilities to build and to keep, as well as to increase the brand equity of their products they offered. There are four purposes of this research; firstly, to examine the influence of brand awareness to the brand equity of Bimoli brand at Indofood Group; secondly, to examine the influence of perceived quality to the brand equity of Bimoli brand at Indofood Group; thirdly, to examine the influence of brand association to the brand equity of Bimoli brand at Indofood Group; and fourthly, to examine the influence of brand awareness, perceived quality and brand association simultaneously to the brand equity of Bimoli brand at Indofood Group. The population of this research is consumers of fried oil of Bimoli who ever buy and consume fried oil of Bimoli brand in towns of Surabaya and Sidoarjo. Samples taken for conducting the research were samples who own population characteristics. Total number of consumer respondent as samples of this research was established at the amount of 130 respondents. Primary data collection for realizing this research was done by distributing questioners to all consumer respondents. It was noted that the sampling method was using non-probability sampling through convenience sampling technique. Technical analyis implemented in this research is statistical formula in this case multiple linear regression model. Through t-test, results of research have proved that brand awareness variable has no impact individually to the brand equity variable, and two variables of perceived quality and brand association have the impact individually to the brand equity variable, and through F-test, the three variables of brand awareness, perceived quality and brand association have the impact simultaneously to the brand equity variable.